Regulation And Implementation of Indonesian Judicial Independence - Tajudin, Ijud (Opción, 2019)
The article’s objective is to explore and analyze the development of regulation Indonesian independence judiciary in every phase of government since Indonesia gained independence in 1945 until the reform era in 1999. Even though 1945 constitutions was stipulated in article 24 that Indonesian judiciary must be free from any kinds of influences, in every phase of gover- nment before reform era, executive directly influenced in regulation or in law enforcement towards independence judiciary. In addition, this paper seeks to analyze whether after reform era Indonesian judges are influenced by Supreme Court when they make decision and how judicial commission role to protect honorable of judges from breach code of judicial conduct. By using descriptive qualitative analysis, the result shows that Indonesia has made regulation to keep independence judicial in1945 Constitution, Law No 48 of 2009, Law No. 35 of 2009. Indonesia has guarantee Independence Judicial through provision. However, there is a space may undirectly influence when judge in district Court or Appeal Court will make decision which is probably a case close to or by order from one of the heads of judicial or non-judicial in Supreme Court. Judge became becarefull in make decision, keep the activities based on code of conduct and attitude guideline of judges inside and outside of the court because under Supreme Court and Judicial Commision surveillance. Some recommendation that can be take into consideration, such as to revise Law No. 18 of 2011 that judicial com- mission could involve in selection candidate district judges with deep inves- tigate about background information candidate district judges and revise Law No.48 of 2009 to make judiciary organitation just like in Netherland which is separated from Supreme Court, concern the administration and management of the organization of the judiciary and independent body for the recruitment/selection of judges (commission for the selection of members of the judiciary) and another independent body for training of judges.